Menerapkan Metode PDCA dalam Menganalisis Strategi Optimasi dan Cost Down dalam Peningkatan Efisiensi Operasional di Perusahaan Otomotif - Intan Mutiara I.; Alya Intan S.; Zharfan R.; Silwa A.; Yudi Prastyo (Journal of Science, Technology, and Innovation, 2025)
This study examines the application of the Plan-Do-Check-Act (PDCA) method in analyzing optimization strategies and cost down initiatives to improve operational efficiency in an automotive company. A qualitative descriptive approach was employed using internal company documents, cost reports, and process improvement records related to packing activities. The findings reveal that the implementation of PDCA enabled the company to identify non-value-added activities, optimize packing materials, and redesign packaging processes without compromising product quality. As a result, annual packing costs were reduced from Rp 65,642,400 to Rp 21,694,500, generating total savings of Rp 43,947,900. The results demonstrate that systematic process evaluation and continuous improvement contribute significantly to cost efficiency and operational stability. Furthermore, the integration of PDCA with cost down strategies strengthens coordination between operational and financial functions, supporting more effective managerial decision-making. This study confirms that PDCA is a practical and replicable framework for enhancing operational efficiency and cost control in the automotive manufacturing industry.